Multiscale influences on extreme winter rainfall in the Philippines. Issue 8 (29th April 2015) - Pullen, Julie; Gordon, Arnold L.; Flatau, Maria; Doyle, James D.; Villanoy, Cesar; Cabrera, Olivia
Abstract During 2007–2008, the Philippines experienced the greatest rainfall in 40 winters. We use a combination of observations (including 48 meteorological stations distributed throughout the islands, Tropical Rainfall Measuring Mission satellite‐sensed precipitation, and shipboard measurements) along with a high‐resolution two‐way coupled ocean/atmosphere model (3 km Coupled Ocean‐Atmosphere Mesoscale Prediction System (COAMPS)®) to examine this anomalous season. As expected from climatology, rainfall was greatest on the eastern side of the archipelago, with seasonal totals exceeding 4000 mm in some locations. A moderate to strong La Niña increased the rainfall across the region. But discrete precipitation events delivered the bulk of the rain to the area and coincided with intense Madden‐Julian oscillation activity over the archipelago and a late February cold surge. General patterns and magnitudes of rainfall produced by the two‐way coupled model agreed with observations from land and from space. During the discrete events, the 3 km COAMPS also produced high amounts of precipitation in the mountainous parts of central Philippines. Direct observations were limited in this region. However, the government reported river flooding and evacuations in Mindoro during February 2008 as a result of significant rainfall. In addition, shipboard measurements from late January 2008 (collected by the Philippines Straits Dynamics Experiment) reveal a fresh lens of water to the west of the island of Mindoro, consistent with high freshwater discharge (river runoff) into the coastal area.